PENGARUH KINERJA KEUANGAN DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN DENGAN CSR DISCLOSURE SEBAGAI PEMODERASI (Studi Empiris pada Perusahaan BUMN yang terdaftar di BEI) - Nurlaila Hasmi (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
The Company was established with the aim to prosper company owners or shareholders by maximizing thecorporate value. The aim of the research was to examine and analyze the effect of financial performance and managerial ownership on corporate value and test the corporate social responsibility disclosure in interaction relationship between financial performance and managerial ownership and corporate value. The research was an empirical study at State Owned Enterprise listed in Indonesia Stock Exchange. The data used were secondary data and the sample were selected using purposive sampling method consisting of 17 companies. They were observed for five years among 22 companies as the populations. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS version 21. There were four proposed hypotheses. The results of the research indicate that financial performance has effect on corporate value, managerial ownership does not affect corporate value, corporate social responsibility disclosure moderates the relationship between financial performance with companies value, and corporate social responsibility disclosure did not moderates the relationship between managerial ownership with corporate value.